A 20-year Journey in Elementary and Early Childhood Science and Engineering Education: A Cycle of Reflection, Refinement, and Redesign - Sandifer, Cody; Lottero-Perdue, Pamela S.; Miranda, Rommel J. (Innovations in Science Teacher Education, 2020)
Over the past two decades, science and engineering education faculty at Towson University have implemented a number of course innovations in our elementary and early childhood education content, internship, and methods courses. The purposes of this paper are to: (1) describe these innovations so that faculty looking to make similar changes might discover activities or instructional approaches to adapt for use at their own institutions and (2) provide a comprehensive list of lessons learned so that others can share in our successes and avoid our mistakes. The innovations in our content courses can be categorized as changes to our inquiry approach, the addition of new out-of-class activities and projects, and the introduction of engineering design challenges. The innovations in our internship and methods courses consist of a broad array of improvements, including supporting consistency across course sections, having current interns generate advice documents for future interns, switching focus to the NGSS science and engineering practices (and modifying them, if necessary, for early childhood), and creating new field placement lessons.